TREND FORECASTING EKSTERNAL MARKETING PADA MARKETPLACE 2023 - Anita Heptariza; Andreas James Darmawan; I Made Satrya Ramayu; Ni Komang Prasiani (Universitas Bina Taruna Gorontalo, 2023)
This research aims as an external marketing tool based on a digital platform-based facility to support multi-user e-commerce, owners and intermediaries. By looking at the development of the trend until the end of this year, the research team aims to provide an overview; direction and the possibility of the hectic trend of moving external marketing strategies or supporting online trade in 2023. The research team's method uses 3T analysis, namely: transpire, trend, and technology; all carried out qualitatively from the literature on the determination of subsequent predictions. The results of the research team are in the form of a new 2023 trend pattern; produced by the research team by collecting literature data and interviews from various sources, focusing on the scope of external marketing to be raised in the evaluation of this research team, namely: brand ambassadors, P.E.L strategy, and customer persona; carry out the formulation of results; and then from the three external scopes of the marketing marketplace, they are explored again to get findings. The implications of the research team's results can be considered, guided, and prepared; both in the academic world with related scientific clusters, as well as in the professional world related to developments and shifts in trends and technology in the digital platform marketplace business.